Study and Review of Ordinary Portland Cement - Swapnil Namdev Sutar; Prajyot Vitthal Patil; Rohit Vitthal Chavan; Mayur M. Maske (ASEAN Journal of Science and Engineering, 2021)
This research aimed to investigate the environmental, economic, and functional performances of ordinary portland cement (OPC). In short, we discussed the definition, the chemical composition and physical performance, and the manufacturing process of OPC. We hope that this paper can be a reference for practitioners and civil engineers.